Determinants of Patient Satisfaction in Primary Healthcare: A Statistical Exploration - Ismail , Moamen Abdelfadil; Albaradi , Khaled Hamad Mohammed; Al-Sobhi, Hanadi Abdul Rahman; Al-Otaibi, Mohammed Tarhib; Alboriadi, Fahad Ali; Tohary, Hassan Ali; Balqasem , Roa’a Adnan; Alkhayat, Haitham Hassan; Alharbi, Bandar Mukhlid Falah; alawad, Raheel Ahmed Abass; Alrashidi, Nouf Muslem (Journal of Ecohumanism, 2024)
Background: Patient satisfaction is a critical measure of healthcare quality, reflecting patients’ experiences and the extent to which their needs and expectations are met. While global studies have identified various determinants of satisfaction, research in some regions, particularly in the Gulf, remains limited. This study investigates the determinants of patient satisfaction in primary healthcare settings, focusing on socio-demographic factors and dimensions of care. Methods: This study was conducted among patients receiving services at primary healthcare centers. A systematic sampling approach yielded 398 completed questionnaires. The instrument assessed six dimensions of satisfaction: interpersonal care, technical competence, accessibility, convenience, availability, and overall satisfaction. Data analysis included descriptive statistics, t-tests, ANOVA, and exploratory factor analysis, with internal consistency measured using Cronbach’s alpha. Results: The mean satisfaction score was 35.2 (SD = 6.8). Married patients and those with college degrees reported significantly higher satisfaction. Factor analysis revealed interpersonal care, accessibility, and technical competence as the most influential dimensions. Communication quality and the time spent with healthcare providers were strongly associated with satisfaction. Approximately 64.8% of participants reported high overall satisfaction. Conclusion: Effective communication and patient-centered interactions are key determinants of satisfaction in primary care. Addressing gaps in provider-patient communication and ensuring sufficient consultation time can enhance patient experiences. These findings emphasize the need for ongoing assessment and improvement of healthcare delivery to meet diverse patient expectations